2013 IEEE International Conference on Green Computing and Communications and IEEE Internet of Things and IEEE Cyber, Physical A 2013
DOI: 10.1109/greencom-ithings-cpscom.2013.268
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Vehicle Route Guidance Based on Connected Vehicles

Abstract: With advances in connected vehicle technology, realtime vehicle route guidance systems gradually become indispensable equipments for drivers. Conventional route guidance systems are designed to direct a vehicle along the shortest path from the origin to the destination without considering the dynamic traffic information. Therefore the state-of-the-art route guidance systems incorporate real-time traffic information to find better paths. So, this paper presents a novel approach to realize the real-time vehicle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Both the public and private sectors are interested in applications and implications of connected vehicles. Applications include intersection signals (Lee and Park, 2012;Christofa et al, 2013;Guler et al, 2014;Hu et al, 2014;Wu et al, 2014;Bagheri et al, 2015;Feng et al, 2015), pavement assessments (Bridgelall, 2013), traffic queue estimation (Li et al, 2013), vehicle routing and travel time estimation (Kianfar and Edara, 2013;Tian et al, 2013;Genders and Razavi, 2015;Moylan and Skabardonis, 2015), driving behavior monitoring and warnings (Sengupta et al, 2007;Goodall et al, 2014;Chrysler et al, 2015;Doecke et al, 2015;Du and Dao, 2015;Osman et al, 2015), and fuel efficiency (Kishore Kamalanathsharma and Rakha, 2014;Liu et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both the public and private sectors are interested in applications and implications of connected vehicles. Applications include intersection signals (Lee and Park, 2012;Christofa et al, 2013;Guler et al, 2014;Hu et al, 2014;Wu et al, 2014;Bagheri et al, 2015;Feng et al, 2015), pavement assessments (Bridgelall, 2013), traffic queue estimation (Li et al, 2013), vehicle routing and travel time estimation (Kianfar and Edara, 2013;Tian et al, 2013;Genders and Razavi, 2015;Moylan and Skabardonis, 2015), driving behavior monitoring and warnings (Sengupta et al, 2007;Goodall et al, 2014;Chrysler et al, 2015;Doecke et al, 2015;Du and Dao, 2015;Osman et al, 2015), and fuel efficiency (Kishore Kamalanathsharma and Rakha, 2014;Liu et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…(iii) Vehicle Route Recommendation. It collects information about just-driven road segments and traffic congestion situations to introduce better routes for drivers based on existing path algorithms [6][7][8][9][10] (all of these route planning algorithms take traffic congestion situations into account in the process of a vehicle route guidance) without presetting the destination beforehand.…”
Section: (I) Driving Route Predictions Based On Hmmmentioning
confidence: 99%
“…(3) foreach (route in ) (4) Starting point = ( 1 , 1 ); (5) End point = ( , ); (6) Insert and into the set ; 7= Filter( ); (8) Cluster Set = -means++ ( ); / * = { [1], [2], . .…”
Section: Parameter Definitions Of a Hmm For Route Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, scholars have begun to study route guidance in a connected vehicle (CV) environment. Tian et al [22] presented a real-time route guidance system based on CV technologies, and simulation results showed that better routes are found using the V2V and V2I technologies. Paikari et al [23] realized CV guidance by developing a V2V and V2I application interface (API).…”
Section: Introductionmentioning
confidence: 99%